2020
DOI: 10.1017/wsc.2020.55
|View full text |Cite
|
Sign up to set email alerts
|

Germination ecology of giant chickweed (Myosoton aquaticum)

Abstract: Giant chickweed [Myosoton aquaticum (L.) Moench], a troublesome broadleaf weed species, is widespread in winter wheat (Triticum aestivum L.) fields in China. However, limited information is available on its seed germination and seedling emergence ecology. Thus, three M. aquaticum populations (JS, HN and AH) from different geographic regions were studied under laboratory conditions to determine the effects of different environmental factors on seed germination or seedling emergence. The seeds germinated at a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Hairy Vetch was found to have inhibitory effects on the growth of harmful weeds due to its strong ability to compete for light, moisture, nutrients, etc., which is based on the release of the allelochemical, cyanamide [ 22 , 82 ]. Additionally, recent research also found that Hairy Vetch is more tolerant and sensitive to osmotic pressure in plantations than many plant species including Capsella bursa-pastoris , Myriophyllum aquaticum, and Avena fatua [ 83 , 84 , 85 , 86 ]. The last among the selected species was Brassica napus L., commonly known as Canola and or Rapeseed, which belongs to the Brassicaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…Hairy Vetch was found to have inhibitory effects on the growth of harmful weeds due to its strong ability to compete for light, moisture, nutrients, etc., which is based on the release of the allelochemical, cyanamide [ 22 , 82 ]. Additionally, recent research also found that Hairy Vetch is more tolerant and sensitive to osmotic pressure in plantations than many plant species including Capsella bursa-pastoris , Myriophyllum aquaticum, and Avena fatua [ 83 , 84 , 85 , 86 ]. The last among the selected species was Brassica napus L., commonly known as Canola and or Rapeseed, which belongs to the Brassicaceae family.…”
Section: Resultsmentioning
confidence: 99%